Minimum anesthetic concentration of isoflurane and sparing effect of midazolam in Quaker parrots (Myiopsitta monachus). (May 2020) - Zaheer, Omar Ahmad; Sanchez, Andrea; Beaufrère, Hugues
Abstract: Objective: To determine the effects of midazolam on the minimum anesthetic concentration (MAC) reduction of end-tidal isoflurane concentration (Fe′ Iso) measured using an electrical stimulus in Quaker parrots ( Myiopsitta monachus ). Study design: Randomized crossover experimental study. Animals: A group of six adult Quaker parrots, weighing 98–124 g. Methods: Birds were anesthetized with isoflurane in oxygen delivered by mask, then tracheally intubated and mechanically ventilated. Three treatments were applied with a 4 day interval between anesthetic events. Each anesthetized bird was administered midazolam (1 mg kg −1 ; treatment MID1), midazolam (2 mg kg −1 ; treatment MID2) or electrolyte solution (control) intramuscularly. The treatments were administered using a replicated Latin square design and the observers were blinded. Based on a pilot bird, the starting Fe′ Iso was 1.8%. After equilibration for 10 minutes, a supramaximal stimulus was delivered using an electrical current (20 V and 50 Hz for 10 ms) and birds were observed for non-reflex movement. The Fe′ Iso was titrated by 0.1% until a crossover event was observed. The MAC was estimated using logistic regression. Results: The MAC of isoflurane (MACISO ) was estimated at 2.52% [95% confidence interval (CI), 2.19–2.85] with a range of 1.85–2.65%. MACISO in MID1 was 2.04% (95% CI, 1.71–2.37) and in MID2 was 1.81% (95% CI, 1.48–2.14); reductions in MACISO from control of 19% ( p  = 0.001) and 28% ( p < 0.001), respectively. Heart rate, temperature, sex and anesthetic time were not different among treatments. Conclusions: Midazolam (1–2 mg kg −1 ) intramuscularly resulted in a significant isoflurane-sparing effect in response to a noxious stimulus in Quaker parrots without observable adverse effects. Clinical relevance: Midazolam can be used as part of a balanced anesthetic approach using isoflurane in Quaker parrots, and potentially in other psittacine species.